The role, benefits and selection of sport psychology consultants: Perceptions of youth-sport coaches and parents. (March 2018) - Thelwell, Richard C.; Wood, Jade; Harwood, Chris; Woolway, Toby; van Raalte, Judy L.
Abstract: Objectives: With practitioners needing to be 'more things to more people', it is essential to understand third-party consumer perceptions of the role and benefits of sport psychology consultants (SPC), and the characteristics that may influence such services being sought. Design: A qualitative thematic analysis approach was used in Study 1 and a cross-sectional conjoint analysis approach was employed in Study 2. Methods: In Study 1, 22 participants (11 youth-sport coaches, 11 parents) took part in semi-structured interviews to investigate, a) understanding the SPC role, b) the benefits of seeking the services of an SPC, and, c) the salient characteristics of an SPC that would influence judgments on preference and likelihood to seek consultant services on behalf of their athlete/child. In Study 2, a total of 115 participants (51 youth-sport coaches, 64 parents) rated 32 practitioner profiles generated from Study 1, with a conjoint analysis employed to determine the relative importance of SPC characteristics. Results: SPCs were viewed by youth-sport coaches and parents as practitioners who can help athletes enhance their performance and well-being, which would be of benefit to athletes. The SPC attribute most important to coaches and parents was interpersonal skills, with a preferred SPC profile also including a high level of experience and training, and a known reputation. Conclusions: SPCs are viewed by youth-sport coaches and parents as experts regarding performance enhancement and well-being. SPCs with strong interpersonal skills, extensive experience and training, and a known reputation are preferred by coaches and parents. Findings reinforce the importance of educating those responsible for the ongoing development of athletes to the role and benefits of SPCs, and for SPC training to ensure that interpersonal skills development opportunities are available. Highlights: Coaches and parents perceive SPCs to improve athletic performance, and athlete well-being. SPCs with strong interpersonal skills, extensive experience, and a known reputation are preferred by coaches and parents. Consumers of sport psychology require ongoing education to the role, and benefits, of SPCs. SPC training must provide opportunities to develop, and demonstrate, interpersonal skills.